Keanekaragaman Jenis dan Sebaran Ikan di Danau Buyan Bali - Taradhipa, I Gusti Agung Dwikhy Oka; Arthana, I Wayan; Kartika, Gde Raka Angga (Current Trends in Aquatic Science, 2018)
Buyan lake is one of the lake in bali, located in pancasari village, sukasada, buleleng. Lack of research on the identification and distribution of fish species in buyan lake. Therefore, it is necessary to conduct research on the identification and distribution of fish species in the buyan lake. This research is take place in pancasari village, sukasada, buleleng. This research is conducted from january to march 2018. Sampling is done 3 times in 3 month. Location determination by using purposive sampling with 4 stations. The fish catch is done by using the gill net with the size 1cm, 5cm and 6,5cm and bubu. The type of fish in this research is 7 type with the total of the catch is 1024 fish. The fish that get biggest share is nyalian srembeng fish that can meet in every research station smallest share is ikan mas that can meet only in station 1, 2 and 3. The variant of fish that located in buyan lake is one of the mid category. uniformity fall into the low category and domination fish include low category.